ANTIFUNGAL OF SOKA FLOWER (Ixora Chinensis Lam.) ETHANOL EXTRACT AGAINST Candida albicans AND Pityrosporum ovale - Keliat, Jane Melita; Sumayyah, Tengku (Talenta Publisher, 2025)
Pathogenic fungi are microorganisms that cause infectious diseases in humans and are capable of growing and developing in various environments. The types of fungi that most often cause skin infections are Candida albicans and Pityrosporum ovale. The soka flower plant (Ixora chinensis Lam.), commonly found in Indonesia, is known to have antibacterial properties. The antifungal strength of the soka flower comes from the natural chemicals in its ethanol extract, which stops the growth of Candida albicans and Pityrosporum ovale. The research method was conducted experimentally, which included stages such as the preparation of dry powder, characterization of dry powder, phytochemical screening both on dry powder and the ethanol extract of soka flowers, preparation of the ethanol extract, standardization of the extract, and evaluation of the antifungal activity of the ethanol extract against both types of fungi. The research results indicate that the minimum inhibitory concentration of the ethanol extract of the soka flower against Candida albicans is 5.5 mg/ml with an inhibition zone diameter of 8.8 mm ±0.05, while for Pityrosporum ovale, the minimum inhibitory concentration is 50 mg/ml with an inhibition zone diameter of 10.7 mm ±0.50. The statistical analysis from Kruskal-Wallis tests show a significant difference in the amounts of ethanol extract from soka flowers based on the size of the inhibition zones for Candida albicans and Pityrosporum ovale, with probabilities of 0.000 and 0.001, both of which are below 0.05.